Intraoperative change in distal motor latency as a predictor for clinical outcome after mini-OCTR: a retrospective cohort study - Mingjie Zhou; Mingjie Zhou; Mingjie Zhou; Mingjie Zhou; Mingjie Zhou; Mingjie Zhou; Chuxiang Chen; Chuxiang Chen; Chuxiang Chen; Chuxiang Chen; Chuxiang Chen; Chuxiang Chen; et al. (Frontiers in Neurology)
IntroductionAlthough mini-open carpal tunnel release (Mini-OCTR) proves to be a standard solution for carpal tunnel syndrome (CTS), precise prediction of recovery remains challenging. The aim of this study was to explore the potential of using intraoperative change in distal motor latency (DML) to predict clinical outcomes.MethodsA retrospective cohort analysis was performed on 52 primary CTS patients, who completed the questionnaires before Mini-OCTR, 1 day (1 day Post-op) and 6 months after Mini-OCTR (6 months Post-op). Latency recovery percent (LRP) was calculated to represent intraoperative change of DML after Mini-OCTR. Multivariate and simple logistic regression analyses were used to quantify the predictive value of LRP on postoperative outcomes.ResultsThe results of patient-reported outcome measures (PROMs) demonstrated that Mini-OCTR was an effective procedure in treating CTS generally with some of the patients experiencing significant improvement in sensory function at 1 day Post-op. Multivariate logistic regression analysis which involves demographic information, CTS-related medical history, electrodiagnostic test results, PROMs and LRP revealed that the prognostic model has high AUC and accuracy, and LRP is a significant predictor among all the involved variables. Simple logistic regression analysis identified an optimal LRP cut-off value of 0.11 for predicting sensory recovery at 1 day Post-op with high accuracy.ConclusionThis study introduces LRP as a practical biomarker that enables surgeons to predict immediate postoperative sensory improvement in Mini-OCTR patients, which can assist surgeons in setting short-term expectations and tailoring postoperative care for the patients.